Mediation Guidance In Avoiding Divorce In Parepare City Religious Courts (Islamic Counseling Guidance Perspectives) - Nasriah Nasriah; Andi Rio Makkulau; Wirani Aisiyah Anwar (IAIN Parepare, 2022)
The Parepare Religious Court has its own meaning in the Mediation Guide, in the mediation orientation process, the Parepare Religious Court refers to Supreme Court Regulation No.1 2016 regarding mediation procedures. In the mediation orientation process, things are done at the Parepare religious court, such as introduction, explaining the purpose of mediation orientation, calculating the problem, providing advice and finally providing a solution, where the mediator (advisor) provides a solution (management advice) or two parts that provide solution (no management), sometimes also a combination of the two focus techniques. If the success of the mediation guidelines is used as a reference to determine the effectiveness of the mediation orientation program in managing divorce cases, then in the Parepare religious court, mediation is not effective. However, the mediation guidance process has been carried out optimally and maximally. This study uses a qualitative method with a descriptive approach and when collecting data using observations, interviews and documentation methods. The data analysis technique used is inductive analysis technique, which means that the data obtained in the field are specifically explained in general words.